ARNTL hypermethylation promotes tumorigenesis and inhibits cisplatin sensitivity by activating CDK5 transcription in nasopharyngeal carcinoma - Hao Peng (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Increasing evidence support an important role for DNA methylation in nasopharyngeal carcinoma (NPC). Here, we explored the role of circadian clock gene Aryl Hydrocarbon Receptor Nuclear Translocator-Like (ARNTL) methylation in NPC. Methods We employed bisulfite pyrosequencing to determine the epigenetic change of ARNTL in NPC cell lines and tissues. ARNTL mRNA and protein expression in cell lines and tissues were detected by real-time PCR and western blotting. Then, we constructed cell lines overexpressing ARNTL and knocked down ARNTL to explore its function and effect on chemotherapy sensitivity of NPC cell lines to cisplatin in vitro and vivo. Finally, we investigated the potential molecular mechanism of ARNTL by gene set enrichment analysis (GSEA), dual Luciferase reporter assay and chromatin immunoprecipitation assay. Results ARNTL was hypermethylated, and its mRNA and protein were significantly down-regulated in NPC cell lines and tissues. When treated by 5-aza-2′-deoxycytidine, mRNA expression was up-regulated. Overexpression of ARNTL could suppress NPC cells proliferation in vitro and vivo while silencing of ARNTL using shRNA achieved opposite results. GSEA assay found that ARNTL was associated with cell cycle and ectopic ARNTL overexpression could induce G2-M phase arrest. Then, we identified and validated cyclin-dependent kinase 5 (CDK5) as the targeting gene of ARNTL by dual Luciferase reporter assay and chromatin immunoprecipitation assay. When transiently infected ARNTL-overexpression cells with PENTER-vector or PENTER-CDK5 plasmids, the later could reverse the suppressive effects of ARNTL on NPC cell proliferation. Moreover, ARNTL significantly enhanced sensitivity to cisplatin in NPC cells. Conclusions ARNTL suppresses NPC cell proliferation and enhances sensitivity to cisplatin by targeting CDK5. ARNTL may represent a novel therapeutic target for NPC.